Dinâmica populacional de Staphylococcus aureus produtor de enterotoxina A inoculado em queijo prato - Pereira, Gisele Inocêncio (2006)
Milk and dairies have constantly been associated with outbreaks of food toxinfections all over the world, Staphylococcus aureus being one of the main responsible for these toxinfections. The importance of S. aureus under the viewpoint of public health has been stood out by their capacity of producing enterotoxins, heat-stable substances, capable of persisting in the final product. This work sought to evaluate the production of enterotoxin A (SEA) in Prato-type cheeses, drawing the profile of the concentration S. aureus and the consequent presence of this enterotoxin distributed spatially in the product throughout the maturation period of the prato cheeses. The cheeses were manufactured by utilizing three treatments: Control, milk inoculated with 103 UFC/mL and milk inoculated with 105 UFC/mL of S. aureus. The certification of the production of staphylococcic enterotoxins was accomplished by the optimum sensitivity in plate (OSP) technique. The results of the counts of Staphylococcus aureus in the cheeses presented no significant difference among the spatial sampling of the cheeses. Also, no significant variation in the population of S. aureus present in the cheeses during all the maturation period occurred. The production of SEA was not detected in any of the treatments performed in this work during maturation period. In general, the production of enterotoxins is detected when the S. aureus population reaches concentrations of 105UFC/g, nevertheless, loss of inoculum utilized occurred in the milk utilized for whey during manufacturing, decreasing the remaining population in the cheese. The pH values of the cheeses and the temperature utilized during maturation enabled the maintenance of the S. aureus population, but they are not considered optimum values for growth and toxin production demanded by these microorganisms. Likely, the adverse conditions as well as the accumulation of by-products as lactic acid produced by yeast bacteria could be acting by interfering or even inhibiting the growth of these microorganisms in prato cheese.